Pelatihan Penyusunan Bahan Ajar Bahasa Indonesia bagi Penutur Asing Berbasis Batik Solo di Chiang Mai University Thailand sebagai Wujud Internasionalisasi Bahasa dan Budaya Indonesia - Kundharu Saddhono; Muhammad Rohmadi; Ani Rakhmawati; Suhailee Sohnui (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
The internationalization of the Indonesian language and culture has become a crucial strategy in strengthening cultural diplomacy in the Southeast Asian region, particularly through the Indonesian Language for Foreign Speakers (BIPA) program. As a strategic partner country, Thailand hosts several universities that offer BIPA programs, including Chiang Mai University. However, a key challenge in implementing BIPA instruction abroad is the limited availability of contextual teaching materials that specifically reflect the richness of Indonesian culture. This study aims to examine the process and outcomes of a training program on the development of BIPA teaching materials based on Solo Batik for students at Chiang Mai University as a concrete form of Indonesia’s language and cultural internationalization. The research employs a descriptive qualitative approach, with data collected through participatory observation during the training sessions, semi-structured interviews with facilitators and participants, and document analysis of the teaching materials developed. The findings reveal that the training not only enhanced students’ understanding of the structure and functions of the Indonesian language but also fostered their appreciation of the cultural values embedded in the motifs, philosophy, and production process of Solo Batik. The students successfully produced creative, contextual, and learner-oriented teaching material prototypes, such as visual modules, interactive dialogues, and culture-based worksheets. These findings highlight the importance of integrating local culture into the development of BIPA teaching materials as an effective strategy for expanding the global reach of the Indonesian language. Consequently, this training serves as a collaborative model that can be replicated in other countries to support the sustainable internationalization of Indonesia’s language and cultural policies.